2015
DOI: 10.1074/jbc.m114.630442
|View full text |Cite
|
Sign up to set email alerts
|

Myeloperoxidase-mediated Methionine Oxidation Promotes an Amyloidogenic Outcome for Apolipoprotein A-I

Abstract: Background: Amyloids made of apolipoprotein A-I (apoA-I) contribute to the growth of the atherosclerotic plaques. Results: ApoA-I methionine oxidation by physiological levels of myeloperoxidase induces amyloid formation. Conclusion: Myeloperoxidase-mediated oxidation not only impairs the physiological functions of apoA-I but also promotes protein loss in form of amyloids. Significance: Our findings identify the physiological mechanism transforming wild-type apoA-I into an amyloidogenic protein.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
84
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 37 publications
(92 citation statements)
references
References 49 publications
7
84
1
Order By: Relevance
“…Future studies will test whether similar factors influence apoA-I misfolding and amyloid deposition upon other mutations or pathogenic modifications, such as Met oxidation in acquired amyloidosis. 17,18 …”
Section: Discussionmentioning
confidence: 99%
“…Future studies will test whether similar factors influence apoA-I misfolding and amyloid deposition upon other mutations or pathogenic modifications, such as Met oxidation in acquired amyloidosis. 17,18 …”
Section: Discussionmentioning
confidence: 99%
“…The only available treatment for AApoAI is end-stage organ transplant. In the acquired form, which is linked to increased plasma triglycerides (TG), aging, and oxidation, full-length apoA-I and its fragments deposit as fibrils in tissues and atherosclerotic plaques ([14, 18-20] and references therein). Such a fiber deposition reduces the mechanical stability of the arterial plaques [21,22], potentially leading to a heart attack or a stroke, and has a range of other pathogenic properties ([1,13,18-20] and references therein).…”
Section: Introductionmentioning
confidence: 99%
“…Alternatively, it is proposed that the mutation-induced structural perturbations in the amyloid-prone regions promote conformational conversions to the ␤-structure in the N-terminal segments (21,22). In addition, it was reported that oxidative modification of apoA-I methionine residues induces transformation of full-length wild-type apoA-I into an amyloidogenic protein (23,24).…”
mentioning
confidence: 99%